2021
DOI: 10.1097/qai.0000000000002578
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Inflammatory Markers by HIV Serostatus and Viral Suppression in a Large Cohort of Patients Hospitalized With COVID-19

Abstract: Background: Limited data exist about clinical outcomes and levels of inflammatory and immune markers among people hospitalized with COVID-19 by HIV serostatus and by HIV viral suppression. Setting: Large tertiary care health system in the Bronx, NY, USA. Methods: We conducted a retrospective cohort study of 4613 SARS-CoV-2 PCR-positive patients admitted between March 10, 2020, and May 11, 2020. We examined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 20 publications
3
49
0
1
Order By: Relevance
“…Whether PWH have elevated risk of severe COVID-19 disease has been under debate, and previous studies provided conflicting evidence on the association of HIV infection with COVID-19 severity 9,15,16,[24][25][26][27][28] . Our results add to a growing body of evidence 13,[28][29][30][31] suggesting that PWH, indeed, have an independent increased risk for severe COVID-19 compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Whether PWH have elevated risk of severe COVID-19 disease has been under debate, and previous studies provided conflicting evidence on the association of HIV infection with COVID-19 severity 9,15,16,[24][25][26][27][28] . Our results add to a growing body of evidence 13,[28][29][30][31] suggesting that PWH, indeed, have an independent increased risk for severe COVID-19 compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al 16 conducted a retrospective cohort study on 4613 COVID-19 positive patients; 100 were PLWH. In an analysis adjusted for age, sex, race/ethnicity, BMI, history of chronic lower respiratory diseases and calendar time, PLWH had an increased risk of intubation compared to PNLWH (aHR 1.73, 95% CI 1.12–2.67; p= 0.01).…”
Section: Methodsmentioning
confidence: 99%
“…SARS-CoV-2 and HIV-1 co-infection and mutual impact Data on the mutual impact of SARS-CoV-2 and HIV-1 co-infections is still unfolding. Early during the COVID-19 pandemic, mixed and partly contrasting results from clinical studies were reported, mainly based on differences in cohort composition, limited co-infection cases per study, and confounding factors, including differences in applied or absent ART [508][509][510]. While an immunocompromised status has been considered a general risk factor for COVID-19, it remained elusive whether the resulting decreased detrimental inflammatory response might even confer beneficial effects and mitigate clinical symptomatic [511][512][513][514][515].…”
Section: Interferon Responsementioning
confidence: 99%